Pengaruh Metode One Day One Ayat (ODOA) terhadap Kemampuan Menghafal Al Qur’an pada Siswa Kelas VI di SDS Terpadu Bina Ilmu Parung – Bogor - Faiz Madani Damanhuri; Sri Nurul Milla; Dewi Anggrayni (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2023)
The method that will be used in this research is the experimental method. The form of the design of this research is the Nonequivalent Control Group Design, which is a research to find the effect of the One Day One verse (ODOA) method on the ability to memorize grade VI students at SD S Terpadu Bina Ilmu Parung-Bogor. In this study, the population was all 6th grade students of SD S Terpadu Bina Ilmu, totaling 60 people. The sample in this study used saturated sampling, which in the sampling technique involved 30 students of class VI A as many as 30 students and students of class VI B as many as 30 students of SD S Terpadu Bina Ilmu Parung-Bogor as samples. In this study, the test was administered twice, namely: first, students were given a pre-test to determine the amount of student memorization in both the control group and the experimental group. Second, students were given a final test (post-test) using the traditional method in the control group and using the ODOA method in the experimental group. The results of the test can be concluded that there is an increase in the ability to memorize the Qur'an for the sixth grade students of SD S Terpadu Bina Ilmu who are taught using the traditional method seen from the average number of memorization before the test is 9.73 and after the test is 13.27 and there is an increase the ability to memorize the Qur'an of class VI SD S Terpadu Bina Ilmu taught by the One Day One Verse method is seen from the average number of memorization before the test is 9.17 and after the test is 16.97. While in the T-Test, there is a difference in the ability to memorize the Qur'an of the sixth graders of SDS Terpadu Bina Ilmu after the One Day One Verse (ODOA) method is applied, as seen from the Paired Sample T Test has a significance of 0.000 <0.05, it can be concluded that The ODOA method can improve the memorization of the sixth graders of SD S Terpadu Bina Ilmu Parung Bogor. Keywords: One Day One Verse (ODOA) method, memorization ability